The hidden stairs and the magic carpet - Abbott, Tony, 1952-; Jessell, Tim.; Copyright Paperback Collection (Library of Congress) (New York : London : Scholastic, 1999)
When Neal and Julie agree to help Eric straighten up his basement, they never imagine that they're in for more than getting a little dusty. But as the three kids follow a soccer ball into the small room under the basement stairs, the floor suddenly evaporates to reveal a rainbow staircase to another world! Before they have a chance to look around, they are caught in the midst of a battle. Shiny red men riding giant lizards are shooting arrows straight at them. They are saved by Princess Keeah of Droon who tells them the red men are warriors for the evil Lord Sparr. She promises to help them get home if they will carry a message for her.
G2
Keywords: Droon (Imaginary place) -- Juvenile fiction; Children's stories